Tradisi Mudik dan Halal Bihalal dalam Pandangan Islam - Hartanto, Rudy; Priyanto, Catur; Mustamik, Khoirul (Lembaga Yasin AlSys, 2025)
Homecoming (Mudik) and Halal Bihalal are significant traditions in Indonesian society, especially during Eid al-Fitr, reflecting social, cultural, and religious values. Mudik, the journey back to one’s hometown, is not only a moment for family reunions but also a symbol of respect for parents and the strengthening of intergenerational bonds. Meanwhile, Halal Bihalal plays a crucial role in maintaining and strengthening social ties through Islamic values such as mutual forgiveness, reinforcing brotherhood, and fostering harmony, even promoting interfaith tolerance. These traditions embody positive values such as mutual cooperation (gotong royong), empathy, and tolerance while serving as a medium for preserving local culture and reinforcing national identity. By integrating moral, spiritual, and communal values, the traditions of Mudik and Halal Bihalal symbolize harmony and strengthen human relationships in a diverse society.